2018
DOI: 10.3390/risks6030093
|View full text |Cite
|
Sign up to set email alerts
|

Linear Regression for Heavy Tails

Abstract: There exist several estimators of the regression line in the simple linear regression: Least Squares, Least Absolute Deviation, Right Median, Theil–Sen, Weighted Balance, and Least Trimmed Squares. Their performance for heavy tails is compared below on the basis of a quadratic loss function. The case where the explanatory variable is the inverse of a standard uniform variable and where the error has a Cauchy distribution plays a central role, but heavier and lighter tails are also considered. Tables list the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…An empirical study conducted by Balkema and Embrechts [15] aimed to assess the performance of various estimators in a simple linear regression problem with deterministic and stochastic components, both modelled as potentially heavy tailed random variables. Balkema and Embrechts showed that under the condition that the deterministic component is of finite variance itself, the least absolute deviation (i.e.…”
Section: On the Validity Of Inferring From The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An empirical study conducted by Balkema and Embrechts [15] aimed to assess the performance of various estimators in a simple linear regression problem with deterministic and stochastic components, both modelled as potentially heavy tailed random variables. Balkema and Embrechts showed that under the condition that the deterministic component is of finite variance itself, the least absolute deviation (i.e.…”
Section: On the Validity Of Inferring From The Resultsmentioning
confidence: 99%
“…Balkema and Embrechts showed that under the condition that the deterministic component is of finite variance itself, the least absolute deviation (i.e. the minimisation of the mean absolute error (MAE)) is typically a good estimator for the linear regression parameters, even if the stochastic component has infinite variance [15]. In the context of stochastic gradient descent, the minimisation of MAE is equivalent to the least absolute deviation.…”
Section: On the Validity Of Inferring From The Resultsmentioning
confidence: 99%
“…Ninth, more broadly, Balkema and Embrechts (2018) provides a review of a substantial literature on robust estimation and heavy tailed data, as well as comparing procedures using Monte Carlo methods. Related work is Kurz- Kim and Loretan (2014).…”
Section: Relating β To Other Estimatorsmentioning
confidence: 99%
“…However, for distributions with infinite mean and/or variance a more powerful approach is needed. We are grateful to an anonymous reviewer for suggesting a comparison with the Theil-Sen estimator, used exclusively to determine linear trends [47]. Its potential limitation is computation time for large data sets.…”
Section: Q Performs Well In Heavy-tailed Noisementioning
confidence: 99%